Analysis of optical gain and attenuation coefficient in erbium–ytterbium-doped sodium-zinc phosphate glasses for integrated photonics applications - Rivera, Frida Lissete Flores; Pérez-Sánchez, Grethell Georgina; Medina-Velázquez, Dulce Yolotzin; Aldaya, Ivan [UNESP]; López, Rodolfo E.; Abreu, Leandra Isabel de [UNESP]; Caldiño, Ulises (Elsevier, 2025)
The search for host glasses capable of incorporating high concentrations of erbium ions has attracted considerable attention, largely due to their straightforward application in integrated photonics. This paper presents a comprehensive characterization of the net gain coefficient in sodium-zinc phosphate glasses doped under four configurations: 1% erbium, and co-doping of 1% erbium with 1% ytterbium. Experimental analysis reveals that all doping configurations exhibit similar attenuation coefficients. For pump power levels between 14.5 and 16.5 dBm, the 1% erbium and 1% erbium-1%ytterbium co-doped samples outperform those doped with 2% erbium and 2% erbium-1%ytterbium in both on–off gain and net gain. Furthermore, while the 1% erbium sample shows a higher net gain up to 16 dBm, the co-doped 1% erbium–ytterbium sample exhibits superior net gain at higher pump power levels.
Keywords: Attenuation coefficients; Integrated photonics; Phosphate glasses